Iowa RBA, May 13, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for May 13, 1996. Highlights of the update include sightings of a Black-headed Grosbeak, Western Tanager, Worm-eating Warbler, Black-throated Blue Warbler, Prairie Warblers, Little Blue Heron, and Red-necked Grebe. Also included are handwritten notes for the next week's update with sightings of several species of Shorebirds such as Marbled Godwits, American Avocets, Dunlins and a Wilson's Phalarope. Epson - sheet feed/flatbed